Kebijakan Pendidikan Di SMA Al-Hidayah Medan - Sri Muliyani; Rifda Ramadina; Said Agil Ad Darain; Nurul Zahara Bancin; Ahmad Mukhlasin (Universitas Maritim AMNI Semarang, 2023)
Education policy is a policy related to the field of education in the process of elaborating the vision and mission of education in order to achieve educational goals through strategic steps in implementing education. This research aims to describe educational policies related to the policy of using different curricula at Al-Hidayah High School in classes X, XI and class XII. However, the researchers here are more focused on discussing the independent learning curriculum. The curriculum used for class X and class XI currently uses the independent learning curriculum, for class XII uses the k13 or kurtilas curriculum. This research uses a qualitative method, descriptive research type. Data was obtained through observation, interviews and documentation techniques by focusing on data regarding the use of the independent curriculum and Al-Hidayah High School as a driving school. The results of the research are that when a school is selected to be a driving school, that school will implement an independent learning curriculum. As a driving school, all policies in learning activities use P5 (Strengthening Pancasila Student Profiles), using student-based learning. So all the provisions relating to the independent curriculum, the implementation carried out at Al-Hidayah High School is in accordance with the school culture and the condition of the existing students' character.